ENHANCING GENERAL LISTENING SKILLS AMONG SCHOOL PUPILS: EFFECTIVE STRATEGIES AND METHODS (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: Enhancing general listening skills among school pupils is crucial for academic success and social interaction. This article explores effective strategies and methods to improve listening comprehension in the school setting. By incorporating interactive activities, creating a supportive learning environment, and providing diverse listening materials, educators can help students develop essential listening abilities. Implementing these approaches can empower students to become active and engaged learners, contributing to their overall academic achievement and personal growth.